2020
DOI: 10.1002/cft2.20069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on the germination of wheat and barley in South Africa

Abstract: Field crops are most susceptible to salt stress in the early stages of growth. There is a general belief that barley (Hordeum vulgare L.) is more salt‐tolerant than wheat (Triticum aestivum L.), yet little is known regarding the response of different South African wheat and barley cultivars to saline conditions. An experiment was conducted to study the effects of salinity on seed germination in three South African spring wheat cultivars (SST 027, SST 056, and SST 087) and three spring barley cultivars (Nemesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Other factors, i.e., water shortage, rainfall limitations, and high evapotranspiration, induced soil salinity in various regions of the globe [27,28]. A high concentration of salts in the soil solution can negatively affect the uptake of water and essential nutrients, reduce plant growth and development, and alter the physiochemical processes (Figure 2) [6,28,29].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Other factors, i.e., water shortage, rainfall limitations, and high evapotranspiration, induced soil salinity in various regions of the globe [27,28]. A high concentration of salts in the soil solution can negatively affect the uptake of water and essential nutrients, reduce plant growth and development, and alter the physiochemical processes (Figure 2) [6,28,29].…”
Section: Figurementioning
confidence: 99%
“…Reducing the α-amylase activity can reduce the sugars translocation into the developing embryo [38]. For example, when wheat and barley seeds were exposed to salt stress, between 40 and 120 nM, germination was reduced by 20% to 40%, while seeds were not germinated with salinity levels of 160-200 nM (Table 1) [27].…”
Section: Seed Germination and Plant Growth Under Salt Conditionsmentioning
confidence: 99%
“…While a plant endures abiotic stress, a variety of genes are switched on or off, leading to changes in many metabolites and proteins, responsible for triggering salinity stress defense [65].…”
Section: Primary Metabolismmentioning
confidence: 99%
“…Podder et al (2020) have reported a similarly reduced mungbean germination under salinity. Decreased seed germination with increased salt concentration was also reported in wheat (Bagwasi et al, 2020) and rice (Öner et al, 2020). Therefore, germination attributes are the most critical and valuable attributes that reflect time, rapidity, uniformity, and synchronization in seed germination under salt stress.…”
Section: Effect Of Salt Stress On Seed Germinationmentioning
confidence: 64%